Jinggangmycin-Induced UDP-Glycosyltransferase 1-2-Like Is a Positive Modulator of Fecundity and Population Growth in Nilaparvata lugens (Stål) (Hemiptera: Delphacidae) - Ge, Lin Quan; Zheng, Sui; Gu, Hao Tian; Zhou, Yong Kai; Zhou, Ze; Song, Qi Sheng; Stanley, David (Frontiers in Physiology, 2019)
UDP-glucuronosyltransferases (UGTs), as multifunctional detoxification enzymes are omnipresent within living organisms, responsible for biotransformation of diverse lipophilic endogenous compounds and phytoalexins in invertebrates. However, the implication of this enzyme family in fecundity of insects remains largely elusive. Here, the underlying mechanisms by which UGT12 involved in Jinggangmycin-enhanced fecundity were investigated. JGM+dsUGT12 treatments resulted in diminished number of eggs laid, oviposition period, JH III (juvenile hormone III) titers, JHAMT (Juvenile hormone acid methyltransferase) and Met (Methoprene tolerant) mRNA level, protein content of fat body and ovary, and population growth, as well as under-developed ovary. Application of JH analog methoprene on the JGM+dsUGT12 treated-females partially rescued the NlVg, NlUGT12 expression, and Vg synthesis. The present results revealed that NlUGT12 may modulate fecundity and population growth of Nilaparvata lugens (Hemiptera: Delphacidae) via regulation of JH and Vg synthesis. These findings not only advance our knowledge towards the mechanisms underlying pesticide-induced pest resurgence, but also yield a novel target for promising pest management.